Kebijakan Indonesia dalam Perlindungan Pencari Suaka dan Pengungsi Pasca Kebijakan Turn Back the Boat Pemerintahan Tony Abbott - Sihombing, Herlina; Farabi, Nadia (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
This research discusess Indonesian policy in protection of asylum seekers and refugees. Since Australia’s turn back the boat policy was issued, the number of asylum seekers and refugees in Indonesia has increased. Indonesia has not refused the arrival of asylum seekers and refugees. As known that Indonesia is not part of state that ratifies the Convention 1951 and Protocol 1967, but Indonesia is willing to accommodate and provide protection to asylum seekers and refugees. Indonesian policy about protection of asylum seekers and refugees in Peraturan Presiden No. 125 Tahun 2016 raises the question, why is Indonesia willing to do that. To explain that, this research will use liberalism theory. Liberalism believes that state is not the unitary actorin the international world, but there are other actors in it. The presence of other actors who play a significant role, has a great influence to state’s policies. This research aims to explain the background of Indonesian policy of provide protection to asylum seekers and refugees. This research also describe Indonesian policies to resolve problem of asylum seekers and refugees in Indonesia.